Development and Implementation of a Mobile Application for Real-Time Geolocation for University Transportation Management - Herrera Rubio, Jorge Enrique; Pedraza López, Natalia; Velandia Narváez, Francisco José (Ingeniería Solidaria, 2025)
Introduction: With the support of technological tools, it is possible to provide practical solutions to address the mobility problems of university transportation services at the University of Pamplona. Objective: The research focuses on optimizing mobility, improving the user experience and ensuring real-time data-driven decision-making through the design, development, and implementation of a mobile application. Method: Four stages are defined: identification, which is carried out through requirements analysis; selection with the use of development tools; development, which establishes the system design; and finally, validation, which verifies the process and its corresponding field validation. Results: The final product is the integration of advanced tools such as Flutter, Firebase, and OpenStreetMap into an application that offers features such as real-time bus tracking, seat availability monitoring, and route management. Conclusions: Finally, it is concluded that it is possible to build an efficient, scalable, and user-centered solution by addressing suggestions during the mobile application development process, using functional and usability testing to meet the requirements according to software evaluation standards and models.